2015
DOI: 10.1371/journal.ppat.1004695
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Regulation of a Legionella pneumophila T4SS Substrate by the Metaeffector SidJ

Abstract: Modulation of host cell function is vital for intracellular pathogens to survive and replicate within host cells. Most commonly, these pathogens utilize specialized secretion systems to inject substrates (also called effector proteins) that function as toxins within host cells. Since it would be detrimental for an intracellular pathogen to immediately kill its host cell, it is essential that secreted toxins be inactivated or degraded after they have served their purpose. The pathogen Legionella pneumophila rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
142
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(160 citation statements)
references
References 50 publications
18
142
0
Order By: Relevance
“…This suggests that SdeA and SidJ are both toxic to yeast when produced at high levels. This observed toxicity and suppression are consistent with recently published data showing a similar relationship between SdeA and SidJ (29).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This suggests that SdeA and SidJ are both toxic to yeast when produced at high levels. This observed toxicity and suppression are consistent with recently published data showing a similar relationship between SdeA and SidJ (29).…”
Section: Resultssupporting
confidence: 93%
“…Thus, the SidE and SidJ proteins are predicted to work in concert to regulate host processes during infection by L. pneumophila. These data are consistent with a recent study that showed a functional interaction between SdeA and SidJ in yeast and on the LCV (29). In addition, we show here that SdeA contains distinct toxicity and SidJ suppression regions.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…However, the complex effector pool of Coxiella undoubtedly modulates additional eukaryotic systems for pathogen benefit such as the cytoskeleton [146], ubiquitination [147] and nuclear processes via the activity of an emerging class of effectors known as nucleomodulins [148,149]. Elucidating signal transduction events that trigger effector translocation, the temporal reliance on effector groups during infection and whether effector-effector regulation occurs [150,151], are of much interest to the field.…”
Section: Future Perspectivementioning
confidence: 99%
“…The underlying molecular mechanisms are poorly defined. SidJ was recently shown to be a metaeffector regulating the LCV localization of the effector SidE and its paralogues, which suggests that its impact on ER recruitment might be indirect (Jeong et al 2015a). Notably, LegK2 possesses autokinase and protein kinase activity in vitro, and this activity is needed to fulfil its role in LCV maturation; however, a host cell target has not yet been identified (Hervet et al 2011).…”
Section: Additional Effectors With Important Roles In Lcv Maturationmentioning
confidence: 99%